2002
DOI: 10.1073/pnas.152318499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on central and peripheral mammalian clocks

Abstract: Circadian organization changes with age, but we do not know the extent to which age-related changes are the result of alterations in the central pacemakers, the peripheral oscillators, or the coupling mechanisms that hold the system together. By using transgenic rats with a luciferase (luc) reporter, we assessed the effects of aging on the rhythm of expression of the Period 1 (Per1) gene in the suprachiasmatic nucleus (SCN) and in peripheral tissues. Young (2 months) and aged (24 -26 months) Per1-luc transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
226
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 282 publications
(253 citation statements)
references
References 54 publications
24
226
1
2
Order By: Relevance
“…Three recent studies have begun to address whether there are changes in molecular rhythm generation in aged animals. In all three studies Period 1 (Per1) and/or Period 2 (Per2) gene expression rhythms were unaffected in the aged SCN [3,19,37]. However, Kolker and colleagues [19] reported that both Bmal1 and Clock expression in the SCN was reduced in aged hamsters.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Three recent studies have begun to address whether there are changes in molecular rhythm generation in aged animals. In all three studies Period 1 (Per1) and/or Period 2 (Per2) gene expression rhythms were unaffected in the aged SCN [3,19,37]. However, Kolker and colleagues [19] reported that both Bmal1 and Clock expression in the SCN was reduced in aged hamsters.…”
Section: Introductionmentioning
confidence: 92%
“…Because aging affects functions regulated by the SCN, it has been suggested that the SCN itself is the primary locus for age-related changes [37]. Indeed, the aged SCN shows a decrease in VIP expression [18], light-induced immediate early gene expression [5,28], and melatonin binding [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, SCN have a reduced expression of two major neurochemical constituents, vasoactive intestinal polypeptide (Chee et al 1988;Krajnak et al 1998), and vasopressin (Roozendaal et al 1987;Cayetanot et al 2005), which accounts to a weakening of SCN interconnections, therefore affecting the circadian clock functionality (Engelberth et al 2013). Current data, however, are focused solely on the aging effects on SCN, which brings a limitation to understand the whole process of aging in CTS (Yamazaki et al 2002;Davidson et al 2008). In view of this absence of data concerning effects of aging in IGL, we documented neurochemical and retinal afferent changes in IGL between young, adult, and aged rats based on GAD, ENK, NPY, and CTb immunoreactivity.…”
Section: Introductionmentioning
confidence: 99%